Diversity of wild edible fruits in the agroforestry area of Cigalontang Village, Tasikmalaya, Indonesia - NENDEN NUR SAYYIDAH KULSUM; RATNA SUSANDARINI (Society for Indonesian Biodiversity, 2023)
Abstract. Kulsum NNS, Susandarini R. 2023. Diversity of wild edible fruits in the agroforestry area of Cigalontang Village, Tasikmalaya, Indonesia. Biodiversitas 24: 4161-4167. Wild edible fruits are non-timber forest products that support the nutritional adequacy of communities around the forest. Scientific inventory and documentation of wild fruit plant diversity are important to reveal local resources' potential in supporting local communities food security. A study on wild edible fruits in the agroforestry area in Cigalontang Village aimed to document the diversity of fruit plant species and traditional knowledge of the community on food plants available from the forest. This study used semi-structured interviews with 63 respondents and guided fieldwork to identify natural habitats and collect specimens of wild edible fruits. The results showed that people of Cigalontang Village commonly consumed 49 wild edible fruit species belonging to 27 families. Zingiberaceae and Moraceae were two families with the highest number of wild edible fruit species mentioned by the respondents. All the fruits were consumed raw as fresh fruits, and some were known as ingredients for traditional medicine to treat minor health complaints. The community discussed the use of wild edible fruits with a review of the nutritional content based on relevant references. Results showed that the community used wild edible fruits for daily nutritional needs, not for sale. Both older and younger generations shared knowledge about the diversity of wild edible fruit plants and were closely related to local traditions kept within the frame of local wisdom. This knowledge, supported by local wisdom held by the community, is important to maintain the sustainability of fruit plant diversity and its conservation.